2018
DOI: 10.1111/bjd.17142
|View full text |Cite
|
Sign up to set email alerts
|

What is behind the ‘swarm of bees’ in alopecia areata

Abstract: Linked Article: Rajabi et al. Br J Dermatol 2018; 179:1033–1048.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“… 9 In what is commonly referred to as a “swarm of bees” on histopathology, inflammatory cells also invade the hair follicle and cause a dysregulation that leads to the clinical presentation of AA. 13 …”
Section: Updates On Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“… 9 In what is commonly referred to as a “swarm of bees” on histopathology, inflammatory cells also invade the hair follicle and cause a dysregulation that leads to the clinical presentation of AA. 13 …”
Section: Updates On Pathogenesismentioning
confidence: 99%
“…9 In what is commonly referred to as a "swarm of bees" on histopathology, inflammatory cells also invade the hair follicle and cause a dysregulation that leads to the clinical presentation of AA. 13 The cytokine interferon-gamma (IFN-γ) and inflammasomes play a significant role in the pathogenesis of AA. C3H/ HeJ is a mouse model, which shows phenotypic, histologic, and immune similarities to human AA.…”
Section: Immunologymentioning
confidence: 99%
“…Diagnosis is nowadays based on dermoscopic identification of black and yellow dots, exclamation mark hairs, broken hairs, short vellus hairs and tapered hairs (Waśkiel et al, 2018). In doubtful cases, a biopsy taken from the margins of an active lesion typically shows the presence of lymphocytes surrounding and invading hair bulbs (Ohyama, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple immunophenotyping studies have suggested the involvement of different T‐helper axes (TH1, TH2, and TH17) in the pathogenesis of AA 3 . CD8+ T cells predominate in the intrafollicular infiltrate and directly attack the follicular epithelium, while CD4+ T cells accumulate mainly in the perifollicular area along with key mediators, such as interferon‐γ, natural killer germline encoded receptor (NKG2D), interleukin‐5(IL5), IL6, IL23, tumor necrosis factor (TNF), and granzymes, all of which have been implicated in the pathogenesis of AA 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…3 CD8+ T cells predominate in the intrafollicular infiltrate and directly attack the follicular epithelium, while CD4+ T cells accumulate mainly in the perifollicular area along with key mediators, such as interferon-γ, natural killer germline encoded receptor (NKG2D), interleukin-5(IL5), IL6, IL23, tumor necrosis factor (TNF), and granzymes, all of which have been implicated in the pathogenesis of AA. 4,5 Although there are several treatment modalities for AA, including topical treatments such as topical and intralesional corticosteroids, minoxidil, topical bimatoprost, systemic treatments such as systemic corticosteroids, photochemotherapy, cyclosporine, methotrexate, sulphasalazine and biologics, the treatment, and prevention of the recurrence of AA are still challenging. 6,7 Topical immunotherapy, such as squaric acid dibutylester (SADBE) and diphencyprone (DPCP), has been suggested as an effective treatment for severe AA.…”
Section: Introductionmentioning
confidence: 99%